The acute myeloid leukemia‐associated Nucleophosmin 1 gene mutations dictate amyloidogenicity of the C‐terminal domain. (8th April 2019) - La Manna, Sara; Scognamiglio, Pasqualina Liana; Roviello, Valentina; Borbone, Fabio; Florio, Daniele; Di Natale, Concetta; Bigi, Alessandra; Cecchi, Cristina; Cascella, Roberta; Giannini, Cinzia; Sibillano, Teresa; Novellino, Ettore; et al.
Abstract : Nucleophosmin 1 (NPM1) is a nucleus‐cytoplasm shuttling protein ubiquitously expressed and highly conserved. It is involved in many cellular processes and its gene is mutated in ~ 50–60% of Acute Myeloid Leukemia (AML) patients. These mutations cause its cytoplasmic mislocation and accumulation (referred to as NPM1c+) and open the door to rational targeted therapy for AML diseases with mutated NPM1 . Currently, there is limited knowledge on the mechanism of action of NPM1c+ and on structural determinants of the leukemogenic potential of AML mutations. Numerous previous studies outlined an unexpected amyloid‐like aggregation tendency of several regions located in the C‐terminal domain that, in wild‐type form, fold as a three‐helical‐bundle. Here, using a combination of different techniques including Thioflavin T fluorescence, congo red absorbance, CD spectroscopy, Scanning Electron Microscopy (SEM) and wide‐angle X‐ray scattering on a series of peptides bearing mutations, we evidence that the amyloidogenicity of NPM1 mutants is directly linked to AML. Noticeably, AML point mutations strongly affect the amyloid cytotoxic effects in neuroblastoma cells and the morphologies of deriving fibrils. This study paves the way to deepen our understanding of AML‐associated NPM1 mutants, and could help to break new ground for the identification of novel drugs targeting NPM1c+ for treatment of AML. Abstract : In this study, we characterize the amyloidogenic potential of different mutations of nucleophosmin1 (NPM1) in its C‐terminal domain helix 3 (H3), mutations which are associated with acute myeloid leukemia (AML). The formation of fibers of H3 mutated peptides is a multi‐step process. Starting from an unfolded state, peptides form protofibrils that over time can generate mature fibers. Subsequently, several fibers can further self‐assemble to form 'fibers of fibers'.